Damage assessment of asphalt concrete with composite additives at the FAM–coarse aggregate interfacial zone. (20th February 2019) - Niu, Dongyu; Chen, Huaxin; Richard Kim, Y.; Sheng, Yanping; Geng, Jiuguang; Guan, Bowen; Xiong, Rui; Yang, Zhengxian
Highlights: The damage at ITZ was identified into adhesive and cohesive damage. The performance of ITZ was evaluated on the initiation and propagation of damages. The strength degradation of ITZ was analyzed. The damages at the ITZ with and without additives were quantitatively assessed. Abstract: Asphalt concrete (AC) is of a three-phase system comprising of coarse aggregate, FAM (fine aggregate matrix) and interfacial zones (ITZ). The interfacial zone between FAM and coarse aggregate plays a critical role which determines the mechanical performance. This paper presents a numerical simulation of the mechanical behavior of ITZ, to quantitatively analyze damage of AC with or without composite additives. The results indicated that damage at the ITZ was initiated from the top area followed by a downward propagation. Both cohesive and adhesive damage of AC with composite additives were less serious than that without composite additives, and the damage severity was greatly affected by the thickness of FAM layer. The most serious damage was observed for the thick FAM layer under a rectangular loading pattern. As such, the adhesive damage area and cohesive damage area of AC with composite additives were found to be 1.7% and 33.8% respectively, less than that without composite additives.